Correction: Potential Cost-Effectiveness of Prenatal Distribution of Misoprostol for Prevention of Postpartum Hemorrhage in Uganda - Lubinga, Solomon J.; Atukunda, Esther C.; Wasswa-Ssalongo, George; Babigumira, Joseph B. (Plos one, 2017)
The correct sentences are “In the base-case analysis, misoprostol distribution lowered the expected incidence of PPH by 1.2% (95% credibility interval (CrI): 0.55%, 1.95%), mortality by 0.08% (95% CrI: 0.04%, 0.13%) and DALYs by 0.02 (95% CrI: 0.01, 0.03).” and “ICERs were US$181 (95% CrI: 81, 443) per DALY averted from a governmental perspective, and US$64 (95% CrI: -84, 260) per DALY averted from a modified societal perspective.”